2016
DOI: 10.21275/art2016929
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adsorption of Cu (II), Pb (II) and Cd (II) Ions onto Acid Activated Watermelon Peels Biomass from Water

Abstract: Abstract:The efficacy of the watermelon peel biomass was tested for the removal of lead, copper and cadmium metal ions using batch experiments. Watermelon peel was first modified by exposing it to1N sulphuric acid. The effect of the treatment on morphological characteristics of the adsorbent was evaluated by mid infrared spectroscopy (MIR) and Scanning Electron Microscopy (SEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Wanja et al [105] similarly obtained 99% of Pb (II) removal using watermelon peel activated carbon as an adsorbent. The pH pzc of the treated sample must be determined to investigate the modification on the surface charge of the sample, .…”
Section: Other Fruits Peel As Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wanja et al [105] similarly obtained 99% of Pb (II) removal using watermelon peel activated carbon as an adsorbent. The pH pzc of the treated sample must be determined to investigate the modification on the surface charge of the sample, .…”
Section: Other Fruits Peel As Adsorbentsmentioning
confidence: 99%
“…At pH > pH pzc, the surface charge is negative, and it may be possible to interact with positive species in solution. For instance, the value of pH pzc of fruit peel wastes such as alkaline modified apricot shell, acidic modified lobeira fruit shell, activated carbon of lemon peel, modified pomegranate peel, mango peel, and the modified grape peel is 5.7, 4, 3.2, 2.35, 4.5, 2.4 and 6.7 respectively [30,95,105,111,114,115]. These values are crucial in the selection of the pH for the adsorption process.…”
Section: Other Fruits Peel As Adsorbentsmentioning
confidence: 99%
“…Thus, the metal ions could not interact with the active site properly. 3,13,26 The previous study found that the pH pzc of sago bark was 5. 20,21 Therefore above this pH, the sago bark surface possesses positively charged 27 .…”
Section: Batch Adsorption Study Effect Phmentioning
confidence: 98%
“…4,5 The adsorption technique is preferred because it is easy operation, high efficiency, low-cost and regeneration ability. 6 The low-cost comes from the utilization of biomass or agricultural waste as adsorbent to remove heavy metals such as barley straw ash 7 , stem tree of soybean 8 , nypa fruticans merr shell 9 , activated carbon from oak leaves 10 and date palm dead leaflets, 11 curry tree carbon, 12 watermelon peel, 13 rice husk, 14 tree sawdust, natural and activated fluorapatite, 15 zeolite, 16 eggshell and sugarcane bagasse. 17 These adsorbents consist of lignocellulosic which has pores, carboxylic and hydroxyl functional group playing a role in metal ion removal.…”
Section: Introductionmentioning
confidence: 99%